A novel methymycin analog, 12-ketomethymycin N-oxide, produced by the heterologous expression of the large pikromycin/methymycin biosynthetic gene cluster of Streptomyces sp. AM4900. Issue 4 (22nd December 2020) - Ueoka, Reiko; Hashimoto, Junko; Kozone, Ikuko; Hashimoto, Takuya; Kudo, Kei; Kagaya, Noritaka; Suenaga, Hikaru; Ikeda, Haruo; Shin-ya, Kazuo
ABSTRACT: A novel methymycin analog, 12-ketomethymycin N -oxide, was produced by the heterologous expression of the pikromycin/methymycin biosynthetic gene cluster of Streptomyces sp. AM4900 together with 12-ketomethymycin, which was only isolated by the biotransformation of the synthetic intermediate before. Their structures were determined by the spectroscopic data and the chemical derivatization. 12-Ketomethymycin showed a weak cytotoxicity against SKOV-3 and Jurkat cells, although its N -oxide analog did not show any activity. Both showed no antibacterial activities against Escherichia coli and Micrococcus luteus . Graphical Abstract: